The Question of Competence : Reconsidering Medical Education in the Twenty-First Century - Lingard, Lorelei; Hodges, Brian David, 1964- (Book collections on Project MUSE., 2012)
Medical competence is a hot topic surrounded by much controversy about how to define competency, how to teach it, and how to measure it. While some debate the pros and cons of competence-based medical education and others explain how to achieve various competencies, the authors of the seven chapters in The Question of Competence offer something very different. They critique the very notion of competence itself and attend to how it has shaped what we pay attention to-and what we ignore-in the education and assessment of medical trainees.Two leading figures in the field of medical education, Brian D. Hodges and Lorelei Lingard, draw together colleagues from the United States, Canada, and the Netherlands to explore competency from different perspectives, in order to spark thoughtful discussion and debate on the subject. The critical analyses included in the book's chapters cover the role of emotion, the implications of teamwork, interprofessional frameworks, the construction of expertise, new directions for assessment, models of self-regulation, and the concept of mindful practice. The authors juxtapose the idea of competence with other highly valued ideas in medical education such as emotion, cognition and teamwork, drawing new insights about their intersections and implications for one another.